2019
DOI: 10.33308/2687248x.201912145
|View full text |Cite
|
Sign up to set email alerts
|

0-6 ay süt çocuklarında inek sütü protein alerjisi varlığının değerlendirilmesi

Abstract: Amaç: Bu çalışmanın amacı anne ve bebeklerin beslenmesi, alerji öyküsü ve bebekte var olan inek sütü protein alerjisi semptomlarını saptamaktır. Aynı zamanda, inek sütü protein alerjisi tanısı alan bebeklerde semptomların sıklığı ve aylık ağırlık kazanımları değerlendirilmektedir. Yöntem: Çalışma, İstanbul ilinde özel bir hastanenin çocuk sağlığı ve hastalıkları anabilim dalına 2018 yılı Ocak-Mart ayları arasında başvuran 0-6 aylık bebeği olan gönüllü 50 anne ile yapılmıştır. Katılımcılara, araştırmacılar tara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the study of Düzgün et al conducted on babies under 6 months of age with a diagnosis of cow's milk protein allergy, it was reported that all babies diagnosed with allergy were born by cesarean section (10). Some studies; suggests that cesarean delivery is associated with subsequent food allergy, particularly in susceptible children.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Düzgün et al conducted on babies under 6 months of age with a diagnosis of cow's milk protein allergy, it was reported that all babies diagnosed with allergy were born by cesarean section (10). Some studies; suggests that cesarean delivery is associated with subsequent food allergy, particularly in susceptible children.…”
Section: Discussionmentioning
confidence: 99%